ESTUDIO COMPARATIVO DE LOS TESTÍCULOS, EPIDÍDIMOS, GLÁNDULAS SEXUALES ACCESORIA S Y ESPERMATOZOIDES EN TRES ESPECIES DE LA GOMORFOS (ROMEROLAGUS DIAZI, LEPUS CA LIFORNICUS Y ORYCTOLAGUS CUNICULUS). - Ambriz García, Demetrio; Contreras Montiel, José Luis; Hernández Pérez, Omar; Merca Dopichardo, Efraín; Cervantes Reza, Fernando A.; Rosado García, Adolfo (Instituto de Ecología, A.C., 2003)
A comparative study of the male reproductive organs and spermatozoa from three lagomorphs species, the volcano rabbit or Zacatuche (Romerolagus diazi), the black-tailed hare (Lepus californicus) and the domestic rabbit (Oryctolagus cuniculus), was conducted. The animals were euthanased and their reproductive organs excised. Testes, epididymes and accessory sexual glands were isolated, removed of any of connective and other tissues and weighed. Caudal spermatozoa were obtained from the epididymal tail, counted, fixed and measured. The testicular mass was not related to body mass, but when considered as a percentage of body mass, the values for L. californicus and R. diazi were twice as large as that determined for O. cuniculus. The epididymal mass, when expressed as a percentage of the body mass, was highest in R. diazi and smallestin O. cuniculus. Spermatozoa counts from the epididymal tail were larger in L. californicus than in R. diazi or O. cuniculus. Lengths and widths of the spermatozoa head from R. diazi were larger than from O. cuniculus and L. californicus. Total length and tail length of caudal spermatozoa from O. cuniculus and R. diazi were found to be similar but larger than those recorded from L. californicus. This is the first such quantitative and comparative study of wild lagomorphs species from North A merica.